Formulasi Sediaan Masker Gel Peel-Off dari Ekstrak Buah Tomat (Solanum Lycopersicum L.) Beserta Uji Aktivitas Antioksidan - Wa Ode Sitti Zubaydah; Selly Septi Fandinata (Journal Syifa Sciences and Clinical Research, 2020)
Tomatoes are well-known as the source of antioxidants due to the content of lycopene, i.e., a potential free radical inhibitor. Gel peel-off masks are among the chemical products containing antioxidants. The first step of the study was extracting tomato fruits by macerating the fruits using alcohol solvents 96%. The obtained thick extract was used as the material of the gel mask; the percentage of the extract comprised 3% (F1), 5% (F2), and 7% (F3), and it used PVA basis 11% and viscolam 3%. According to the result, the gel peel-off masks meet the requirements of physical and storage stability evaluation. The result of the antioxidant test reveals that the IC50 value of the three masks is F1 189.22 µg/mL, F2 89.34 µg/mL, and F3 36.77 µg/mL. Further, the result of T-Test reveals that P-value = 0.019 (α = 0.05), indicating a difference in the result of the antioxidant test of the three formulae in day one (t0) and day 28 (t28).